2020
DOI: 10.1089/cyber.2020.0394
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Well-Being Among Asians/Asian Americans During COVID-19: The Role of Social Media

Abstract: Since the outbreak of COVID-19, Asians and Asian Americans have been experiencing an uptick of discrimination. With most people experiencing months of lockdowns, social media may become a particularly important tool in Asian people's coping with discrimination. Grounded in the multiactivity framework of social media use, this study explored whether experience with discrimination was associated with more social media use among Asian people and how adaptive social media use was for their well-being during COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 41 publications
4
55
0
Order By: Relevance
“…This finding is in line with emerging research underscoring the importance of technology during the COVID-19 pandemic to maintain social connection, and, in turn, protect mental health. 17,18,27 It also supports the wellestablished stress-buffering hypothesis, indicating that social…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This finding is in line with emerging research underscoring the importance of technology during the COVID-19 pandemic to maintain social connection, and, in turn, protect mental health. 17,18,27 It also supports the wellestablished stress-buffering hypothesis, indicating that social…”
Section: Discussionsupporting
confidence: 70%
“…[24][25][26] Indeed, research during COVID-19 found that active forms of social media use (private messaging and both posting and commenting) were associated with increased perceived social support, and in turn greater well-being, whereas passive use (browsing social media) was not. 27 These results suggest that to maintain a sense of social connection and to buffer the potential negative effects of isolation, it may be beneficial for individuals to actively maintain online social connection.…”
Section: Introductionmentioning
confidence: 89%
“…There is growing evidence that various forms of support provided by others, including a sensitivity to suffering, may help buffer negative mental health outcomes [ 43 , 44 ]. For example, Asians who experienced COVID-19-related discrimination reported fewer negative mental health outcomes when others provided emotional and social support [ 45 ]. Further, people may report less pain when others empathize with their suffering [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is the reassurance from authorities that will temper the fears of tourists and reduce their worries. Second, tourists who suffer from discrimination may resort to social media as a means to receive social support (Yang et al, 2020). On one hand, positive interaction with friends online allows them to share their experiences and keep connected and updated in disorienting times; on the other hand, it enables catharsis leading to resonance and understanding.…”
Section: Managerial Implicationsmentioning
confidence: 99%